The Influence of Plyometrics Training and Reaction Time on Serang – Hindar Ability on Pesilat (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The background of the problem is the low serang - hindar ability of the fighter, the purpose of this study is to determine and analyze the effect of plyometrics training, namely single leg bounding and double leg speed hops, analyze the effect of high and low reaction time, analyze the effect of plyometrics training with reaction time and analyze the interaction between plyometrics training and reaction time on the attack-avoidance ability of the fighter. This study uses an experimental method with a 2x2 factorial design, the data analysis technique uses Analysis of Variance (Anova) at a significant level of (0.005). The population in this study were 24 fighters. The sampling technique used total sampling with a sample of 24 fighters. The results of this study:1. To analyze between single leg bounding and double leg speed hop exercises with a significant value of sig (0.000) < (0.005) and a value of Fcount 18.730 > Ftable 0.250. 2. To analyze between high and low reaction times on the ability to attack - hinder the fighter with an average value of sig (0.000) < (0.005) and a value of Fcount 12.992 > Ftable 0.250. 3. To analyze the single leg bounding exercise with high and low reaction times on the attack-avoidance abilities of the fighter with an average pre-test score of 55.83 > 49.58 and post-test 73.42 > 64.00. 4. To analyze the double leg speed hop exercise with high and low reaction times on the serang - hindar ability of the fighter with an average pre-test value of 47.08 > 37.08 and post test 78.33 > 67.92. 5. To analyze the interaction between plyometrics training and reaction time on the serang - hindar ability of the fighter with a value of sig (0.915) > (0.005) and an Fcount of 0.552 > Ftable 0.250. Based on this research, plyometric exercises, namely single leg bounding and double leg speed hop exercises can improve serang - hindar abilities, high reaction times are better than fighters with low reaction times.